The Devil You Know: Self-Esteem and Switching Responses to Poor Service - Consiglio, Irene; van Osselaer, Stijn M J (Journal of Consumer Research, 2019)
Abstract We investigate a psychological factor regulating consumers’ switching in response to poor service quality: chronic global self-esteem. Whereas high-self-esteem consumers tend to switch to other providers in response to poor service quality, low-self-esteem consumers often do not. This happens because low-self-esteem consumers who experience poor service become risk-averse, and therefore reluctant to engage in new committed service relationships. Indeed, low-self-esteem consumers’ likelihood to switch to an alternative provider in response to poor service quality increases when this provider offers a less risky, low commitment (vs. more risky, high commitment) contract. Moreover, experimentally reducing low-self-esteem consumers’ risk aversion increases their likelihood to switch to alternative providers in response to poor service quality. Finally, low-self-esteem consumers’ risk aversion mediates their reluctance to switch in response to poor service. We rule out failure severity perceptions, power, autonomy, affect, and action orientation as alternative explanations. The implication of this research for public policy makers is that promoting competition (by offering consumers options and by reducing switching costs) may not be enough to protect the welfare of low-self-esteem consumers. We also suggest ways in which firms can untie vulnerable consumers from negative service relationships.